The Combination of Ankle Pumping Exercise and 30˚ Leg Elevation on Foot Edema in Chronic Kidney Disease - Nursanti, Afrilia; Rosyida, Ratna Wirawati; Setyorini, Yuyun (poltekkes kemenkes mataram, 2024)
Chronic kidney disease is a condition in which progressive and irreversible kidney function disorders occur that the body fails to maintain metabolism, fluid, and electrolyte balance. Excess fluids and electrolytes in the body can cause circulation overload and edema. Edema not handled properly can cause complications in various body systems. Treatment that can be to reduce edema can be pharmacology and non-pharmacological. One of the non-pharmacological methods is ankle pumping exercise therapy with a combination of 30˚ leg elevation. To find the effectiveness of giving ankle pumping exercise therapy with a combination of 30° leg elevation to reduce the degree of edema in chronic kidney disease patients. This study used a randomized controlled trial (RCT) research design with a pre-posttest design with a control group. The number of samples is 58. Sampling uses probability sampling with a simple random sampling technique. The results of the Wilcoxon statistical test in the control group obtained significant results of 0.083 (p-value> 0.05), and the intervention group obtained significant results of 0.000 (p-value <0.05). The Mann-Whitney test found a difference between the two groups with a significance result of 0.000 (p-value <0.05). Ankle pumping exercise therapy with a combination of 30° leg elevation effectively reduces the degree of edema in chronic kidney disease patients.